2020
DOI: 10.1002/ana.25754
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Magnetic Resonance Imaging Outcome Predictors in Pediatric Anti–N‐Methyl‐D‐Aspartate Receptor Encephalitis

Abstract: Objective To evaluate disease symptoms, and clinical and magnetic resonance imaging (MRI) findings and to perform longitudinal volumetric MRI analyses in a European multicenter cohort of pediatric anti–N‐methyl‐D‐aspartate receptor encephalitis (NMDARE) patients. Methods We studied 38 children with NMDARE (median age = 12.9 years, range =1–18) and a total of 82 MRI scans for volumetric MRI analyses compared to matched healthy controls. Mixed‐effect models and brain volume z scores were applied to estimate long… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
27
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 32 publications
5
27
0
8
Order By: Relevance
“…Although brain lesion distributions have been found to differ between MOGAD and AQP4-NMOSD patients, brain MRI volumetry did not show any differences in MOGAD patients compared to healthy controls in whole brain, deep grey matter, or white matter volumes (100,103). In children with ADEM, reduced brain volume and failure of age-expected brain growth was found for both MOG-IgG seropositive and -seronegative patients (Bartels et al submitted), similar to findings in paediatric anti-NMDA-receptor encephalitis and paediatric-onset MS (7,81,104).…”
Section: Advanced Mri Techniquessupporting
confidence: 70%
See 1 more Smart Citation
“…Although brain lesion distributions have been found to differ between MOGAD and AQP4-NMOSD patients, brain MRI volumetry did not show any differences in MOGAD patients compared to healthy controls in whole brain, deep grey matter, or white matter volumes (100,103). In children with ADEM, reduced brain volume and failure of age-expected brain growth was found for both MOG-IgG seropositive and -seronegative patients (Bartels et al submitted), similar to findings in paediatric anti-NMDA-receptor encephalitis and paediatric-onset MS (7,81,104).…”
Section: Advanced Mri Techniquessupporting
confidence: 70%
“…In paediatric MOG-associated autoimmune encephalitis, cerebral MRI findings include extensive cortical and/or subcortical grey matter involvement without the typical white matter lesions seen in ADEM (4,60). Importantly, cerebral MRI in these children was normal in only 9% of the cohort, which is much less compared to other types of autoimmune encephalitis, such as anti-NMDA-receptor encephalitis where MRI can be normal in around 50% of the patients (81). In young children presenting with the rare leukodystrophy-like MOGAD phenotype, cerebral MRI shows extensive confluent symmetrical white matter lesions with progression over time (61).…”
Section: Cerebral Mrimentioning
confidence: 92%
“…Bacchi et al (33) showed that in children with head MRI abnormalities, the incidence of disturbance of consciousness, probability of recurrence, and Glasgow severity score was higher than in those displaying a normal head MRI. Bartels et al (34) reported that 39.5% of the children with anti-NMDA receptor encephalitis had abnormal MRI findings, mainly white matter hyperintensities at T2/fluid-attenuated inversion recovery. MRI showed an abnormality in 52.9% of the children in this study, consistent with Dalmau et al (12).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal mag netic resonance imaging findings, a clinical presentation with sensorimotor deficits, and a treatment delay exceeding 4 weeks were associated with worse clinical outcomes in 38 children with antiNMDAR encephalitis. 9) The central nervous system (CNS) is considered an immune privileged organ, but recent research revealed that it is an active…”
mentioning
confidence: 99%
“…Overall, outcomes in children are usually good, although this varies by the underlying tumor type and stage as well as the severity of the initial neurological symptoms and timing of the initial treatments. Abnormal magnetic resonance imaging findings, a clinical presentation with sensorimotor deficits, and a treatment delay exceeding 4 weeks were associated with worse clinical outcomes in 38 children with anti-NMDAR encephalitis [ 9 ].…”
mentioning
confidence: 99%